Plant Genetic Resources Network in East Asia: Proceedings of the meeting for the Regional Network for Conservation and Use of Plant Genetic Resources in East Asia, 13-16 August 2001, Ulaanbaatar, Mongolia - Zangh, Z.; Zhou, M.; Ramanatha Rao, V.; International Plant Genetic Resources Institute (2002)
The Regional Network for Conservation and Use of Plant Genetic Resources in East Asia (EA-PGR) was established in 1991 and has provided an effective mechanism for sharing and exchanging information, discussing and identifying common interests, and initiating and developing collaborative activities among member countries including China, Japan, Republic of Korea, Democratic People's Republic of Korea and Mongolia. IPGRI East Asia Office services as interim secretariat of the network and works closely with the national coordinators for implementing collaborative programmes initiated by the network involving several member countries. Examples of such collaborative activities are the studies on adzuki bean genetic diversity and collecting and characterization of millet genetic resources. These have played a critical role in enhancing sharing of resources, information and technologies for implementing the Global Plan of Action (GPA) among member countries of the network through joint activities on research, training and germplasm exchange. The current proceedings is the result of the meeting of the Regional Network for Conservation and Use of Plant Genetic Resources in East Asia held in Ulaanbaatar, Mongolia, 13- 16 August 2001. The meeting aimed to exchange views on current status of the conservation and use of plant genetic resources (PGR) in each country and improve mutual understanding, review the progress of joint activities in the region, and identify priority areas for future collaboration.